Neutrophil Transmigration Mediated by the Neutrophil-Specific Antigen CD177 Is Influenced by the Endothelial S(536)N Dimorphism of Platelet Endothelial Cell Adhesion Molecule-1 - Bayat, Behnaz (2010)
The human neutrophil-specific adhesion molecule CD177 (also known as the NB1 alloantigen) becomes upregulated on the cell surface in a number of inflammatory settings. We recently showed that CD177 functions as a novel heterophilic counterreceptor for the endothelial junctional protein PECAM-1 (CD31), an interaction that is mediated by membrane-proximal PECAM-1 IgD 6, which is known to harbor an S(536)N single nucleotide polymorphism of two major isoforms V(98)N(536)G(643) and L(98)S(536)R(643) and a yet-to-be-determined region on CD177. In vitro transendothelial migration experiments revealed that CD177(+) neutrophils migrated significantly faster through HUVECs expressing the LSR, compared with the VNG, allelic variant of PECAM-1 and that this correlated with the decreased ability of anti-PECAM-1 Ab of ITIM tyrosine phosphorylation in HUVECs expressing the LSR allelic variant relative to the VNG allelic variant. Moreover, engagement of PECAM-1 with rCD177-Fc (to mimic heterophilic CD177 binding) suppressed Ab-induced tyrosine phosphorylation to a greater extent in cells expressing the LSR isoform compared with the VNG isoform, with a corresponding increased higher level of β-catenin phosphorylation. These data suggest that heterophilic PECAM-1/CD177 interactions affect the phosphorylation state of PECAM-1 and endothelial cell junctional integrity in such a way as to facilitate neutrophil transmigration in a previously unrecognized allele-specific manner.